Gender, ethnicity and familial ideology in Georgetown, Guyana : household structure and female labour force participation reconsidered - Trotz, Alissa (1996)
Questions some of the assumptions lying behind the projected relationships between the domestic domain and female employment. Examines how ethnicity intercedes in household organisation and women's labour market behaviour. Argues that analyses of patriarchy which prioritise gender at the expense of other social constructs through which women's experiences are refracted as ultimately unable to offer an explanatory framework which can adequately account for the production of similarities and differences among women